Examples and Non-examples as a Road to Understanding the Concept of Function - Eka Resti Wulan; Yulia Izza El Milla (EduMa: Mathematics education learning and teaching, 2020)
This qualitative study aims to describe the conceptual understanding of prospective mathematics teachers at STKIP PGRI Lumajang by determining examples and non-examples of functions. This research was conducted by giving tests and interviews with 12 subjects. Data were analyzed using Miles & Huberman model. Â This study showed that the subjects investigated whether paired to determine a given statement is a function or not. Subjects focus on specific expressions, e.g., or others that they have previously recognized as a function. However, some subjects used the vertical line test to determine a given graph represents a function or not, although they were unable to explain why the vertical line test was the appropriate method. Their understanding is limited to procedural knowledge such as mental representations and incomplete concept images, then failing to be comprehensively linked to the definition of the concept of functionÂ